Analisis Stabilitas pada Lereng dengan Perkuatan Tanaman Vetiver Menggunakan Metode Elemen Hingga 3D - Hamdhan, Indra Noer; Pratiwi, Desti Santi; Rahmah, Rizka Adisya Kamila (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
A landslide is the downslope movement of a soil mass or rock or debris of both (Bobrowski and Highlind, 2008). One of the measures to mitigate slope erosion that causes landslide is by applying bio-engineering system using a vegetation called Vetiver (Vetiveria Zizanioides). The purpose of  this study is to analyze slope stability with a vegetation system using PLAXIS 3D software based on finite elements method and referring to the guidelines from the Ministry of Public Works and Housing with the title Guidelines for Vetiver Grass Planting for Surface Erosion Control and Prevention of Shallow Landslides on Road Slopes.The result shows that the deeper the Vetiver root modelled will increase the value of the safety factor, reinforcement using vegetation is effective on 30° slopes in PLAXIS 3D. The percentage increase in the value of the safety factior generated by PLAXIS 3D is 10.94%.